2018
DOI: 10.1166/jnn.2018.15717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal (Mn, Co, Zn, Ni) Doping on Structural, Optical and Photocatalytic Properties of TiO2 Nanoparticles Prepared by Sonochemical Method

Abstract: Metal-doped TiO2 nanoparticles (Metal = Mn, Co, Zn, Ni) were synthesized by sonochemical method accompanying post calcination process using metallic nitrates of manganese, cobalt, zinc, nickel with various metal contents from 0-5 mol% and titanium isopropoxide as a starting precursors. Sodium hydroxide (NaOH) base was used as a precipitating agent. The influence of ultrasound operated at 750 W 20 kHz on the crystalline structure of metal-doped TiO2 nanoparticles has been characterized by X-ray diffraction (XRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…An increase in the dopant concentration has shown increase in the absorbance in the visible spectrum Energy band gap of the prepared samples was estimated by Tauc's formula αhν = A(hν-E g ) n where hν is the photon energy, αis the linear absorption coefficient, A is the proportionality constant and Eg is the bandgap energy and n= 1/2 for direct or n = 2 for indirect allowed transition semiconductors [30]. The energy band gap of the samples were derived by taking the intercept of the tangent to the plots of (αhν) 2 versus photon energy (hν) [12] as shown in Fig. 7.…”
Section: Uv-vis Diffuse Reflectance Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the dopant concentration has shown increase in the absorbance in the visible spectrum Energy band gap of the prepared samples was estimated by Tauc's formula αhν = A(hν-E g ) n where hν is the photon energy, αis the linear absorption coefficient, A is the proportionality constant and Eg is the bandgap energy and n= 1/2 for direct or n = 2 for indirect allowed transition semiconductors [30]. The energy band gap of the samples were derived by taking the intercept of the tangent to the plots of (αhν) 2 versus photon energy (hν) [12] as shown in Fig. 7.…”
Section: Uv-vis Diffuse Reflectance Spectramentioning
confidence: 99%
“…The doped ions contribute additional energy levels, trapping more electrons and holes at the surface and causing a shift in the absorption edge towards the visible region of the spectrum [10,11]. Zinc (Zn), nickel (Ni), cobalt (Co) [12,13] manganese (Mn) [12], barium (Ba), palladium (Pd) [14,15], iron (Fe) [16], copper (Cu), silver (Ag) [15], chromium (Cr) [15,17] metals when doped in TiO 2 exhibited a red shift in the absorption edge, enhancing the photocatalytic activity of TiO 2 . Metal-doped TiO 2 has, however, been reported to have a number of adverse effects, including thermodynamic instability, a boost in electron-hole recombination centers, the insolubility of the dopants, and fluctuations in the diffusion length of the charge carriers [18].…”
Section: Introductionmentioning
confidence: 99%
“…Element doping can also efficiently enhance photocatalytic performance. For instance, Junlabhut et al 75 reported the synthesis of transition metal-doped TiO 2 nanoparticles (NPs) using a sonochemical method. The method employed NaOH as a precipitant and utilized titanium isopropoxide, along with nitrates of Mn, Co, Zn, and Ni, as raw materials.…”
Section: The Principle Of Sonochemical Synthesismentioning
confidence: 99%
“…[1,8] However, the wide bandgap energy of TiO 2 (E g � 2.0-3.2 eV) and rapid recombination of photogenerated charge carriers limits its photocatalytic efficiency to only the UV range of light, which make up only about 3-5% of the whole solar light spectrum. [8] To extend the light absorption range, prolong the lifetimes of photoexcited electron-hole pairs and enhance the photocatalytic activity of TiO 2 , various strategies have been employed, such as surface modification, [10] bandgap engineering by doping with a transition metals (Cr, Mn, Co, Zn, Ni, Fe) [11][12][13] and non-metals (N, P, S, C, B, etc. ), [14][15][16][17] plasmonic coupling (Au, Ag, Pt and Pd) [18][19][20][21] and coupling with other semiconductors (ZnO, WO 3 , SrTiO 3 , SnO 2 , CdS, ZnS, CdSe, Cu 2 O and MoS 2 ).…”
Section: Introductionmentioning
confidence: 99%